The Effect of Immigration on Wages: Exploiting Exogenous Variation at the National Level - Joan Llull (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This paper estimates the effect of immigration on native wages at the national level taking into account the endogenous allocation of immigrants across skill cells. Time-varying exogenous variation across skill cells for a given country is provided by interactions of push factors, distance, and skill cell dummies: distance mitigates the effect of push factors more severely for less educated and middle experienced. Because the analysis focuses on the United States and Canada, I propose a two-stage approach (Sub-Sample 2SLS) that estimates the fiist stage regression with an augmented sample of destination countries, and the second stage equation with the restricted sub-sample of interest. I derive asymptotic results for this estimator, and suggest several applications beyond the current one. The empirical analysis indicates a substantial bias in estimated OLS wage elasticities to immigration. Sub-sample 2SLS estimates average - 1:2 and are very stable to the use of alternative instruments.
Keywords: J31; J61; 330; Immigration; Wages; Sub-Sample Two Stage Least Squares